The adoption of human resource practices to support employees affected by intimate partner violence: Women representation in leadership matters - Chan‐Serafin, Suzanne; Sanders, Karin; Wang, Lu; Restubog, Simon Lloyd D. (Human Resource Management, 2023)
AbstractIntimate partner violence (IPV) is a global public health issue that negatively impacts organizations and their employees. Research suggests that organizations can play a supportive role to lessen this negative impact. However, it has been relatively silent on the conditions under which organizations choose to play such a role. Integrating social role and critical mass perspectives, we examine the extent to which organizations adopt human resource (HR) practices to support employees affected by IPV. Specifically, we argue that organizations are more likely to adopt IPV‐related HR practices when they are led by female Chief Executive Officers (CEOs) and Top Management Teams (TMTs) with more female members. Furthermore, we argue that when women's representation reaches a critical mass plateau, appointing more women in TMTs has no incremental impact, and this non‐linear relationship moderates the CEO gender effect. Overall, we found support for our hypotheses based on a survey study of HR professionals from 414 Australian organizations (Study 1) and an archival study using 2 years of the Workplace Gender Equality Agency data from 4186 Australian organizations (Study 2). Theoretical and practical implications on the influence of gender configurations in leadership positions on the adoption of diversity, equity, and inclusion‐related HR practices are discussed.